2021
DOI: 10.3390/su13041695
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Safety Model for Pedestrian Red-Light Running at Signalized Intersections in China

Abstract: The traditional way to evaluate pedestrian safety is a reactive approach using the data at an aggregate level. The objective of this study is to develop real-time safety models for pedestrian red-light running using the signal cycle level traffic data. Traffic data for 464 signal cycles during 16 h were collected at eight crosswalks on two intersections in the city of Nanjing, China. Various real-time safety models of pedestrian red-light running were developed based on the different combination of explanatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The authors observed that red light signals were more often violated by oncoming pedestrians when neighbours were doing the same in Kolkata city, India. Wu et al [27] developed a real-time safety model to investigate red-light running violations in the city of Nanjing, China. The results showed that pedestrian red-light running is statistically significantly associated with pedestrian volume, the ratio of males to females, the proportion of pedestrians on phones talking, pedestrian waiting time, green ratio, signal type, and length of the crosswalk.…”
Section: Impact Of Distracted and Violating Behaviour Of Pedestrians ...mentioning
confidence: 99%
“…The authors observed that red light signals were more often violated by oncoming pedestrians when neighbours were doing the same in Kolkata city, India. Wu et al [27] developed a real-time safety model to investigate red-light running violations in the city of Nanjing, China. The results showed that pedestrian red-light running is statistically significantly associated with pedestrian volume, the ratio of males to females, the proportion of pedestrians on phones talking, pedestrian waiting time, green ratio, signal type, and length of the crosswalk.…”
Section: Impact Of Distracted and Violating Behaviour Of Pedestrians ...mentioning
confidence: 99%
“…Keegan and O'Mahony [16] highlighted in their research that 35% of pedestrians cross against a red light. Studies confirm that pedestrians who cross against a red light are exposed to a higher accident risk [15,16]. In addition, King et al [17] determined that pedestrians who crossed against the red light accounted for 13% of the overall percentage of pedestrians at signalised intersections, and there were approximately eight times as many crashes per crossing event as there were legal crossings.…”
Section: Introduction 1backgroundmentioning
confidence: 98%
“…This can be explained by the fact that neither drivers nor pedestrians follow the rules of traffic light signalling. Studies have shown that the most common pedestrian offences are illegal crossings during a red-light phase [10][11][12][13][14][15]. Keegan and O'Mahony [16] highlighted in their research that 35% of pedestrians cross against a red light.…”
Section: Introduction 1backgroundmentioning
confidence: 99%